Performance Analysis of Regular and Irregular Horizontal Multi-Story Buildings Structure - Fernando, Figo; Sahputra, Deded Eka; Fatchurrohman, Nanang (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2025)
This study investigates the effect of building shape on seismic performance in earthquake-prone areas such as Padang City. Using the Indonesian seismic standard SNI 1726:2019, three multi-story reinforced concrete buildings were modeled: a square (regular), a rectangular (regular), and an irregular plan. The analysis focused on internal forces, base shear, displacement, and drift ratio to evaluate differences in structural response. Results show that buildings with horizontal irregularities experience higher internal forces and displacements. The bending moments in irregular buildings are 4.84% higher than in rectangular buildings and 10.07% higher than in square buildings. Base shear is 1.53% and 3.04% higher, respectively. The maximum displacement differences reach 0.93 m (X direction) and 0.54 mm (Y direction). The average drift ratio in the X direction is about 0.56% for all models, while square-shaped buildings show smaller Y-direction drift. These findings highlight that plan irregularities significantly influence seismic performance, providing insights for safer structural design in seismic regions.